Carboplatin: molecular mechanisms of action associated with chemoresistance (Brazilian Journal of Pharmaceutical Sciences, 2014)
Carboplatin is a derivative of cisplatin; it has a similar mechanism of action, but differs in terms of structure and toxicity. It was approved by the FDA in the 1980s and since then it has been widely used in the treatment of several tumor types. This agent is characterized by its ability to generate lesions in DNA through the formation of adducts with platinum, thereby inhibiting replication and transcription and leading to cell death. However, its use can lead to serious inconvenience arising from the development of resistance that some patients acquire during treatment, limiting the scope of its full potential. Currently, the biochemical mechanisms related to resistance are not precisely known. Therefore, knowledge of pathways associated with resistance caused by carboplatin exposure may provide valuable clues for more efficient rational drug design in platinum-based therapy and the development of new therapeutic strategies. In this narrative review, we discuss some of the known mechanisms of resistance to platinum-based drugs, especially carboplatin.